Attenuated afferent inhibition correlated with impaired gait performance in Parkinson’s disease patients with freezing of gait - Wen, Puyuan; Zhu, Hong; Liu, Zaichao; Chang, Amin; Chen, Xianwen (Frontiers in Aging Neuroscience, 2024)
BackgroundThe neural mechanisms underlying freezing of gait (FOG) in Parkinson’s disease (PD) have not been completely comprehended. Sensory-motor integration dysfunction was proposed as one of the contributing factors. Here, we investigated short-latency afferent inhibition (SAI) and long-latency afferent inhibition (LAI), and analyzed their association with gait performance in FOG PD patients, to further validate the role of sensorimotor integration in the occurrence of FOG in PD.MethodsTwenty-five levodopa responsive-FOG PD patients (LR-FOG), fifteen levodopa unresponsive-FOG PD patients (LUR-FOG), twenty-eight PD patients without FOG (NO-FOG PD) and twenty-two healthy controls (HC) were included in the study. Clinical features such as PD motor symptoms, FOG severity and cognitive abilities were evaluated using clinical scales in subjects with PD. All participants underwent paired associative stimulation (PAS) to evaluate SAI and LAI in addition to regular input-output curve by transcranial magnetic stimulation. The performances of gait were assessed using a portable gait analyzing system in 10-meter timed Up and Go task. The correlations between the gait spatiotemporal parameters or the scores of FOG scale and the magnitudes of SAI or LAI were analyzed.ResultsCompared to HC and NO-FOG PD patients, SAI was decreased in FOG PD subgroups. LAI was also reduced in both LR-FOG PD and LUR-FOG PD in relative to HC; however, only LUR-FOG PD showed significant reduction of LAI in comparison to NO-FOG PD group. FOG PD patients showed poorer gait performance compared to HC and NO-FOG PD group. The reduction of SAI and LAI were correlated with the impaired gait spatiotemporal parameters or scores of FOG scale in PD with FOG.ConclusionThe SAI and LAI were attenuated in PD patients with FOG, and the reduction of SAI or LAI were correlated to disturbed gait performance, indicating that sensory-motor integration dysfunction played a role in the development of FOG in PD.